Snakebite presenting as acute coronary syndrome: An interesting diagnosis and management - Patial, Abhimanyu; Patial, Purnima; Sharma, Aradhna; Sharma, Tarun; Kapoor, Dhiraj (Indian Journal of Case Reports, 2019)
Snakebite is a common presentation in India, especially in the Sub-Himalayan region. The most common presentation of snakebiteis neurotoxic and hematologic complications. Acute coronary syndrome after a snakebite is rare. This case report explicitly explainsa patient presenting as acute coronary syndrome after a snakebite with dynamic electrocardiogram changes. Later on, the anti-snakevenom therapy was given to the patient and her condition improved. It should be kept in mind that, since the pathology of snakebiteinducedmyocardial infarction is different, its management will also be different.